Time-loss injuries in karate: A prospective cohort study of 4 consecutive World Karate Championships - Augustovicová, D.; Lystad, R. P.; Arriaza, R. (Orthopaedic Journal of Sports Medicine, 2019)
Background: Prospective studies on injuries in martial arts competitions are scarce, especially those involving time-loss injuries. The upsurge of karate athletes competing in top-level karate competitions warrants elucidation of the time-loss injury risk.